The R∞ property for Houghton's groups - Jang Hyun Jo; Jong Bum Lee; Sang Rae Lee (Algebra and Discrete Mathematics, 2017)
We study twisted conjugacy classes of a family of groups which are called Houghton's groups Hn (n∈N), the group of translations of n rays of discrete points at infinity. We prove that the Houghton's groups Hn have the R∞ property for all n∈N.